Project-Based Learning in Dance Education: Its Implementation Among Tenth Grade Students at Brawijaya Health Vocational High School, Tulungagung - Isabella Zalia Fatmasari; setyo yanuartuti (Universitas Negeri Surabaya, 2025)
This study aims to analyze the implementation of Project-Based Learning in dance education for Grade X students at SMK Kesehatan Brawijaya Tulungagung and to describe its contribution to the students' learning process. The study is motivated by the implementation of the Merdeka Curriculum, which emphasizes student-centered learning through the development of creativity, collaboration, communication, and critical thinking skills. Dance education requires a learning model that provides active learning experiences, enabling students not only to understand theoretical concepts but also to produce creative works through a structured learning process. This study employed a descriptive qualitative approach. The research was conducted at SMK Kesehatan Brawijaya Tulungagung. The participants consisted of a dance teacher and Grade X students who participated in dance learning using the Project-Based Learning model. Data were collected through observation, interviews, and documentation. Data trustworthiness was ensured through source triangulation and technique triangulation. Data analysis involved data reduction, data display, and conclusion drawing. The study focused on the implementation of the Project-Based Learning syntax, including project selection, project planning, scheduling, project implementation, project presentation, and learning evaluation. This study is expected to provide a comprehensive description of project-based dance learning, identify the supporting and inhibiting factors affecting its implementation, and explain its contribution to students' learning processes. The findings are expected to serve as a reference for teachers in developing dance learning practices that are appropriate for the characteristics of vocational high school students.